A cohort study of circulating progenitor cells after ST-segment elevation and non-ST segment elevation myocardial infarction in non-diabetic and diabetic patients - Baumbach, Andreas; Cui, Yu-Xin; Evans, Rebecca N.; Culliford, Lucy; Johnson, Tom; Rogers, Chris A.; Reeves, Barnaby C.; Bucciarelli-Ducci, Chiara; Harris, Jessica; Hamilton, Mark; Madeddu, Paolo (Frontiers in Cardiovascular Medicine, 2022)
Background: Myocardial infarction induces elevation of progenitor cells in the circulation, a reparative response inhibited by type-2 diabetes. Objectives: Determine if myocardial infarct severity and diabetes interactively influence the migratory activity of CD34+/CXCR4+ progenitor cells and if the migratory test predicts cardiac outcomes. Methods: A longitudinal study was conducted on patients with or without diabetes with a STEMI or NSTEMI. CD34+/CXCR4+ cells were measured in the peripheral blood using flow cytometry, and migratory activity was tested in vitro on cells isolated from samples collected on days 0 and 4 post-infarct. Cardiac function was assessed at three months using cardiac MRI. Results: Of 1,149 patients screened, 71 (6.3%) were eligible and consented. Fifty had STEMI (16 with diabetes) and 21 NSTEMI (8 with diabetes). The proportion of CD34+/CXCR4+ cells within blood mononuclear cells was 1.96 times higher after STEMI compared with NSTEMI (GMR=1.96, 95% CI 0.87, 4.37) and 1.55 times higher in patients with diabetes compared to patients without diabetes (GMR=1.55, 95% CI 0.77, 3.13). In the latter, STEMI was associated with a 2.42-times higher proportion of migrated CD34+/CXCR4+ cells compared with NSTEMI (GMR=2.42, 95% CI 0.66, 8.81). In patients with diabetes, the association was the opposite, with a 55% reduction in the proportion of migrated CD34+/CXCR4+ cells. No statistically significant associations were observed between the frequency in peripheral blood or in vitro migration capacity of CD34+/CXCR4+ cells and MRI outcomes. Conclusions: We document the interaction between infarct and diabetes on the migratory activity of CD34+/CXCR4+ cells. The test did not predict functional outcomes in the studied cohort.